Pragmatics and Analytical Philosophy: Foundation and Concept - Hefiani, Sandra (Journal of Human Sciences, 2023)
There has been a lot of talk lately about pragmatics and its various applications; what is its concept? What are its mechanisms? What are the issues it studies? Here we decided to talk about the concepts of this approach, and search for its philosophical references, specifically analytical philosophy law.